The discovery and design of novel HIV-1 capsid modulators and future perspectives. (2nd January 2023) - Ding, Dang; Xu, Shujing; Zhang, Xujie; Jiang, Xiangyi; Cocklin, Simon; Dick, Alexej; Zhan, Peng; Liu, Xinyong
ABSTRACT: Introduction: Although combination antiretroviral therapy (cART) has achieved significant success in treating HIV, the emergence of multidrug-resistant viruses and cumulative medication toxicity make it necessary to find new classes of antiretroviral agents with novel mechanisms of action. With high sequence conservation, the HIV-1 capsid (CA) protein has attracted attention as a prospective therapeutic target due to its crucial structural and regulatory functions in the HIV-1 replication cycle. Area covered: Herein, the authors provide a cutting-edge overview of current advances in the design and discovery of CA modulators, PF74, GS-6207 and their derivativeswhich targets a therapeutically attractive NTD-CTD interprotomer pocket within the hexameric configuration of HIV-1 CA. The discovery and development of these compounds, and derivatives thereof, have provided valuable information for the design of second-generation CA-targeting antivirals. Expert opinion: Despite some successes in designing and discovering HIV-1 CA modulators, more studies are required to decipher which chemical groups confer specific desirable properties. The future of CA-modulating compounds may lie in covalent inhibition and the creation of proteolysis-targeting chimeras (PROTACs). Moreover, biological interrogation of the process of CA uncoating, virus–host interactions, and studies on the lattice-binding restriction factors may improve our knowledge of HIV-1 CA and support the design of new antiviral agents.